2011
DOI: 10.1074/jbc.m110.168526
|View full text |Cite
|
Sign up to set email alerts
|

An Archaeal tRNA-Synthetase Complex that Enhances Aminoacylation under Extreme Conditions

Abstract: Aminoacyl-tRNA synthetases (aaRSs) play an integral role in protein synthesis, functioning to attach the correct amino acid with its cognate tRNA molecule. AaRSs are known to associate into higher-order multi-aminoacyl-tRNA synthetase complexes (MSC) involved in archaeal and eukaryotic translation, although the precise biological role remains largely unknown. To gain further insights into archaeal MSCs, possible proteinprotein interactions with the atypical Methanothermobacter thermautotrophicus seryl-tRNA syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 56 publications
2
42
0
Order By: Relevance
“…Using the Y2H methodology we found that the archaeal SerRS can interact with ribosomal proteins and ArgRS. [113] We found that the key functional outcome of the complex formation between ArgRS and SerRS in archaea is its stimulating effect on the rate of serylation. The optimal activity of SerRS is achieved in a complex with ArgRS at 200-300 mM NaCl and at the temperature of 65 °C which is in accordance with the growth of M. thermautotrophicus under elevated osmolarity and temperature.…”
Section: Macromolecular Interactions Of Atypical Serrsmentioning
confidence: 95%
See 1 more Smart Citation
“…Using the Y2H methodology we found that the archaeal SerRS can interact with ribosomal proteins and ArgRS. [113] We found that the key functional outcome of the complex formation between ArgRS and SerRS in archaea is its stimulating effect on the rate of serylation. The optimal activity of SerRS is achieved in a complex with ArgRS at 200-300 mM NaCl and at the temperature of 65 °C which is in accordance with the growth of M. thermautotrophicus under elevated osmolarity and temperature.…”
Section: Macromolecular Interactions Of Atypical Serrsmentioning
confidence: 95%
“…Our data support the notion that SerRS:ArgRS complex may constitute a part of the thermoand osmoadaptation mechanisms of thermophilic methanogenic archaea, by providing an optimal microenvironment for the tRNA aminoacylation under a wide range of conditions. [113] Beside ArgRS, the Y2H screen identified the ribosomal protein L3 as a SerRS interactor, indicating a possible interaction of the archaeal aaRSs with the ribosome. In further characterization of interactions of archaeal aaRSs with the ribosome we showed by microscale thermophoresis (MST) that atypical SerRS and an archaeal ArgRS bind to the large ribosomal subunit with micromolar affinities.…”
Section: Macromolecular Interactions Of Atypical Serrsmentioning
confidence: 99%
“…This step largely depends on dissociation rates. 39 Besides proteins it is possible to immobilize various lipid membrane systems and in this way study protein-membrane interactions and even elucidate mechanisms of pore formation for many important molecules. [40][41][42] The method is often applied in drug discovery, since the technology has evolved enormously towards high-throughput instrumentation.…”
Section: Methodsmentioning
confidence: 99%
“…Both types of enzymes bind one or two cognate tRNAs across two protein subunits, 12,15 and it seems that in both systems tRNA binding is enhanced by the interaction of SerRSs with other proteins. 6,16 We have previously shown that yeast SerRS (a bacterial-type enzyme) associates with peroxin Pex21p, 16 while SerRSs from methanogens form assemblies with arginyl-tRNA synthetase (ArgRS). 6 In this paper we present further evidence that interaction of MtSerRS and tRNA…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we previously explored the ability of seryl-tRNA synthetases (SerRSs), which catalyze esterification of cognate tRNA Ser isoacceptors with serine, to interact with other aaRSs and with nonsynthetase proteins. 6 Although, generally, the aaRSs that recognize the same amino acid are rather conserved in terms of sequences and 3D-structures in all domains of life, the two diverged types of SerRSs exist. [7][8][9][10] Bacterial-type SerRSs function in a variety of archaeal, bacterial and eukaryotic organisms, while somewhat atypical, methanogenic-type SerRS was found only in methanogenic archaea, 10,11 the organisms which often inhabit the environments characterized by extreme living conditions (anaerobic, thermofilic, psychrophilic, halophilic).…”
Section: Introductionmentioning
confidence: 99%